The Effects of COVID-19 Pandemic on Spanish Protected Areas: the Case of Picos de Europa National Park - Molteni, Carla Maria (2022)
Protected areas are complex social-ecological systems; thus, they were unavoidably impacted by COVID-19. Spain is one of the most diverse countries in terms of biodiversity in the European Union and the second most visited country in 2019 and third touristic destination worldwide. Understanding the effects of the pandemic in Spanish protected areas is very important to discuss new possibilities on how to drive sustainable development on these conserved spaces and how to manage them in the event of external shocks and uncertain scenarios. Therefore, the aim of this study is to have a better understanding of the effects and opportunities of the pandemic on Spanish protected areas. To address this concern, a qualitative analysis is conducted based on an assessment of secondary literature and relevant interviews. Picos de Europa national park was chosen as case study because of its unique features. This study shows the drawbacks of the pandemic in Picos de Europa in terms of management operations, drastic fluctuation of visitors, loss of tourism revenues, vulnerability of neighboring communities, missed opportunities in conservation and education and pressure on nature. On the other hand, it poses opportunities in terms of technology, innovation, fundings, lessons learned, rise in educational and conservation activities and more awareness on the environment and rural surroundings. This study suggests that is difficult to find a win-win solution that includes the targets of nature conservation, viability of local economies and tourism activities in Picos de Europa. Ideas for management options that focus on dealing with the negative outcomes of the pandemic are suggested.